Uma inquietação entre o indivíduo e o espaço. Distância, vazio, imagem. - André Rodrigues Marques (2013)
The aim of the present work is to reflect on the restlessness between the individual and the space. We consider essential the understanding of the notions of distance, emptiness and image, since these are necessarily implicit in the relationship between the existence of self, the others and the things. Under this assumption we propose four possible fields for reflection: existence, space, image and desire. Throughout all the argument we try to demonstrate the close contact between each of these fields, because we consider the inseparability between them, as well as the necessary overlap that, between themselves, they all entail. We believe that the meditation on the restlessness previously enunciated is urgent: it seeks to settle the possibility of understanding the real, the criticism of contemporary image and the true values of architecture. We view the approach of critical image as very important for the understanding of reality, but it does not materialize into an obsession of evidence; it has the ability to subvert the illusions of the moment we live